The impact of neighborhood characteristics on routine and gang-involved gun violence: are structural covariates salient? - Stripling, Dana (Deviant behavior, 2025)
An extensive body of literature has described the influence of neighborhood characteristics, including socio-economic deprivation, residential turnover, and racial/ethnic composition on gun crime. There have been limited efforts, however, to examine the extent to which these effects might vary based on the nature of gun crime - particularly in communities outside of major cities like Chicago or St. Louis. This study attempts to address this issue through application of negative binomial regression and equality of coefficients tests to data obtained from the crime logs and American Community Survey data of a medium-sized city in the Southeastern U.S. Specifically, this study examines (in)equality in the structural covariates of gun crimes when these offenses are disaggregated by gang-involved gun crime versus non-gang-involved gun crime across a sample of 153 census block groups in Chattanooga. Results indicate that the relative influence of neighborhood structural characteristics varies, to some extent, by type of gun crime, illustrating the need for disaggregated measures as a matter of exploring relationships between sub-crime types.